Acts of Care - Ritchey, Sara (Cornell University Press, 2021)
"Brings together the histories of European medicine, gender, and Christianity to re-embed women's participation in medieval healthcare. Using devotional manuscripts, hagiographical texts, liturgy, poetry, and medical treatises, it reveals the healthcare knowledge and caregiving practices of Cistercian nuns and beguines in the late medieval Lowlands" Provided by publisher.